THE BASIS OF TEACHING SPEAKING IN LITERATURE - Usarov Ravshan Xudayorovich (International Engineering Journal For Research & Development, 2021)
This article deals with the main language skills. One of the basic language skill is speaking. In this article we try to explain teaching speaking in literature.